2016
DOI: 10.1016/j.cub.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionarily Conserved Plant RKD Factor Controls Germ Cell Differentiation

Abstract: In contrast to animals, in which the germ cell lineage is established during embryogenesis, plant germ cells are generated in reproductive organs via reprogramming of somatic cells. The factors that control germ cell differentiation and reprogramming in plants are poorly understood. Members of the RKD subfamily of plant-specific RWP-RK transcription factors have been implicated in egg cell formation in Arabidopsis based on their expression patterns and ability to cause an egg-like transcriptome upon ectopic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 31 publications
4
112
0
Order By: Relevance
“…After fertilization more neck cells expressed trpVNS ( Figure S3D), suggesting a possible function of MpRKD in spermatocyte interaction or attraction. Indeed, such a function is supported by an independent study, reporting that sperm attraction to archegonia depends on MpRKD [21].…”
Section: Mprkd Is Broadly Expressed In the Gametophytic And Sporophytmentioning
confidence: 63%
See 2 more Smart Citations
“…After fertilization more neck cells expressed trpVNS ( Figure S3D), suggesting a possible function of MpRKD in spermatocyte interaction or attraction. Indeed, such a function is supported by an independent study, reporting that sperm attraction to archegonia depends on MpRKD [21].…”
Section: Mprkd Is Broadly Expressed In the Gametophytic And Sporophytmentioning
confidence: 63%
“…Thus, MpRKD may be required for the maintenance of egg cell differentiation and/or quiescence, which may be tightly linked to each other, as they are in A. thaliana pollen development, where DUO1 and DUO3 play an analogous role to that of RKD-type genes in terms of proliferation and differentiation [33,34]. On the other hand, an involvement of MpRKD in cell fate specification is substantiated by the observations that MpRKD is required for sperm proliferation and differentiation during M. polymorpha male gametogenesis [21] and that the basal cell in Atrkd4 mutant embryos in A. thaliana differentiates normally and expresses cell-specific markers, but subsequently loses its fate and basal cell fate markers disappear [35]. The small protrusions around the rim of the cavity containing the gemmae in amiRNA-transformed M. polymorpha plants could represent an analogous example for initiation of a cell fate that is later aborted due to the lack of MpRKD function.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In fact, Marchantia encodes a single RKD copy only, advancing loss-of-function studies. Rövekamp et al (2016) and Koi et al (2016) generated RNAi and recombination-induced mutants, respectively. Both studies report defects in egg cell development.…”
Section: Genes Involved In the Specification Of Individual Cell Typesmentioning
confidence: 99%
“…In addition, the WUS clade was the latest derived lineage in the phylogenetic tree of WOX family genes (Figure 4D), which is consistent with previous findings in Arabidopsis as well as other plants (Lian et al, 2014). The RKD family of plant RWP-RK factors is expressed in reproductive cells of land plants, and has a single origin (Koi et al, 2016). In the gene trees (Figures 4B,C), AcRKD resided in the RKD clade corresponding to the RKD subfamily designated by Chardin et al (2014); AcLBD is located in the Class IB LBD gene lineage, which was reported to be involved in root development (Coudert et al, 2012; Chanderbali et al, 2015).…”
Section: Discussionmentioning
confidence: 99%